2017
DOI: 10.20321/nilejbe.v3i7.120
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital as a Competitive Advantage in Pan African Nigeria Limited, Abuja

Abstract: <p class="Default">The study examines the relationship between intellectual capital and competitive advantage in Pan African Nigeria Limited, Abuja.  The study also sought to find out how intellectual capital (human capital, social capital, relational capital and structural capital) enhances competitive advantage in Pan African Nigeria Limited, Abuja. The population of 65 employees were used and the population was used as sample size.  Point in time data were collected from primary source and Ordinary Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similarly, Morris and Lewis (1995), Lerner (2000) and Fini et al (2009) also discussed the importance of government support in shaping entrepreneurial intentions. The research also discusses the role of the political environment in determining intentions supporting the findings of Opusunju et al (2018). However, in the current study impact of the conflict was included in this variable and the score was found to be above average (mean = 3.77).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Similarly, Morris and Lewis (1995), Lerner (2000) and Fini et al (2009) also discussed the importance of government support in shaping entrepreneurial intentions. The research also discusses the role of the political environment in determining intentions supporting the findings of Opusunju et al (2018). However, in the current study impact of the conflict was included in this variable and the score was found to be above average (mean = 3.77).…”
Section: Discussionmentioning
confidence: 54%
“…The second important antecedent of entrepreneurial intention, therefore, in this study represents the contextual elements. It has been seen that entrepreneurs depend on environmental conditions, which influence various aspects of entrepreneurial activity (Opusunju et al, 2018). In this dimension, the role of government policies, the influence of the political environment and economic conditions of a particular region are included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They conclude that macroeconomic indices like interest and inflation rates display instantaneous reactions from their foreign counterpart impulses in advanced economies. Opusunju et al (2020) examined the Nigeria and India trade relations for 20 years between 1999 and 2018 using ex-factor design. The data obtained from the National Bureau of Statistics were analyzed using Microsoft Excel and statistical package for social sciences.…”
Section: Review Of Literaturementioning
confidence: 99%